Processing sweet potato flour - Carvalho, Maria da Piedade M. de; Moura, Layde L.; Pape, Gunther (Pesquisa Agropecuaria Brasileira, 2014)
An analysis of sweet potato flour produced by the same process as cassava flour, to campare the two products with respect to whole meal and total carbohydrate production as well as to nutritional value, yield, and nutrient losses - proteins, sugar and mineral salts - occurring during processing. llicing the roots, without pressing, followed by drying, milling and sifting, is suggested as a way of classifying the flour. The output of sweet potato flour by this process is higher than of cassava flour. Sweet potato produces more carbohydrates than cassava or maize. Drying at 50°C improves the final product.